THE EFFICACY OF ANTIHYPERTENSIVE TREATMENT COMBINATION WITH ANXIOLYTICS IN HYPERTENSIVES WITH ANXIETY DISORDER - D. V. Kovalev; V. V. Skibitsky; A. N. Kurzanov; A. I. Ponomareva (Российский кардиологический журнал, 2017)
Aim. To compare the influence of the simple and combined with anxiolytic drug tofisopam (AT) antihypertesion therapy (AHT) on the 24-hour blood pressure (BP) profile, anxiety level and life quality of patients with uncontrolled arterial hypertension and anxiety spectrum disorder.Material and methods. Sixty-nine patients (mean age 48,5±5,3 y. o., 35 women) were randomized to 2 groups. Each group consequently during 1 year study received two types of medicines for 6 months each with cross-replacement: isolated AHT and combination AHT with AT (AHT+A). Group 1 (35 persons) for the 1st half year took AHT, and then following half year AHT+A; group 2 (34 persons) — in back order. At the end of every period the following parameters were controlled: ambulatory blood pressure monitoring, prominence of trait and reactive anxiety, and life quality. Also, the same comparisons were done for every group separately at the end of the first and second stages of treatment.Results. The initiation of combination AHT+A led to faster decrease of BP, achievement of lower mean daily and mean nocturnal systolic and diastolic BP, lower BP variability parameters. Only combination AHT+A showed adequate reducement of reactive anxiety. Combination and simple AHT in 6 months led to significant improvement of life quality, however combination AHT showed more significant values.Conclusion. Efficacy of combination AHT+A in hypertensive persons with anxiety disorder is higher comparing to simple AHT.